2018
DOI: 10.1002/adom.201801071
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Thermally Activated Delayed Fluorescence into Mechanochromic Luminescent Emitters: High‐Performance Solution‐Processed Yellow Organic Light Emitting Diodes

Abstract: emitting diodes (OLEDs). [6] Very recently, thermally activated delayed fluorescence (TADF) emitters have emerged as a potential alternative to phosphorescent emitters for OLEDs due to their abilities to reach unity internal electroluminescence quantum efficiency without using noble metals. [7] Thanks to the continuous endeavor of investigators, lots of highefficient TADF emitters have sprung up in the past years. [8] However, the multicolor TADF emitter of which the solid state emission could be reversibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Most recently,Y ang andc o-workers developed as eries of TADF-active multicolor-changing MCL materials based on the D-A scaffold by using diphenyl [1,2,4]triazolo[1,5-a]pyrimidine (TzPm) as an acceptora nd phenoxazine as ad onor (Figure 35 a). [111] On doping in CBP matrix (0.7 wt %d oping), all of the compounds showedt ypical TADF properties, with yellow emissions (l em = 527-543 nm, t d = 2-3 ms), narrow DE ST values (60-100 meV), and good F PL values (0.49-0.66, under an argon atmosphere). OLED devices that were fabricatedb yu sing solution processes based on the configuration ITO/PEDOT:PSS/ emitter in CBP (0.7 wt %)/PmPyPB/Liq/Al showedy ellow EL, with peaks within the range l = 542-560 nm and good maxi-mum EQEs of 9.3-14.3%.I nterestingly,D -A compound 7TzPmPXZ exhibited bicolor (yellow-orange) MCL behavior, whereas compounds that contained more donor units (5TzPmPXZ and 5,7TzPmPXZ)s howed tricolor-changing MCL behavior in response to av ariety of external stimuli,s uch as grinding, heating, recrystallization, and solvent fuming (yellow-yellowish-orange-orangeand yellow-red-deep-red, respectively; Figure 35 b-d).…”
Section: Tadf-active Multicolor-changing MCL Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…Most recently,Y ang andc o-workers developed as eries of TADF-active multicolor-changing MCL materials based on the D-A scaffold by using diphenyl [1,2,4]triazolo[1,5-a]pyrimidine (TzPm) as an acceptora nd phenoxazine as ad onor (Figure 35 a). [111] On doping in CBP matrix (0.7 wt %d oping), all of the compounds showedt ypical TADF properties, with yellow emissions (l em = 527-543 nm, t d = 2-3 ms), narrow DE ST values (60-100 meV), and good F PL values (0.49-0.66, under an argon atmosphere). OLED devices that were fabricatedb yu sing solution processes based on the configuration ITO/PEDOT:PSS/ emitter in CBP (0.7 wt %)/PmPyPB/Liq/Al showedy ellow EL, with peaks within the range l = 542-560 nm and good maxi-mum EQEs of 9.3-14.3%.I nterestingly,D -A compound 7TzPmPXZ exhibited bicolor (yellow-orange) MCL behavior, whereas compounds that contained more donor units (5TzPmPXZ and 5,7TzPmPXZ)s howed tricolor-changing MCL behavior in response to av ariety of external stimuli,s uch as grinding, heating, recrystallization, and solvent fuming (yellow-yellowish-orange-orangeand yellow-red-deep-red, respectively; Figure 35 b-d).…”
Section: Tadf-active Multicolor-changing MCL Materialsmentioning
confidence: 96%
“…Most recently, Yang and co‐workers developed a series of TADF‐active multicolor‐changing MCL materials based on the D–A scaffold by using diphenyl [1,2,4]triazolo[1,5‐ a ]pyrimidine (TzPm) as an acceptor and phenoxazine as a donor (Figure a) . On doping in CBP matrix (0.7 wt % doping), all of the compounds showed typical TADF properties, with yellow emissions ( λ em =527–543 nm, τ d =2–3 μs), narrow Δ E ST values (60–100 meV), and good Φ PL values (0.49–0.66, under an argon atmosphere).…”
Section: Multifunctional Emittersmentioning
confidence: 99%
“…N.B . All photophysical studies in toluene Rajamalli et al, 2016 ; Ganesan et al, 2017 ; all photophysical studied on neat film Chen et al, 2018 ; Zhan et al, 2019 ; all photophysical studies in DCM Takeda et al, 2018 ; all photophysical studies in their respective solid states/crystalline states (Zhang et al, 2017 ; Huang et al, 2018 ; Data et al, 2019 ; Zheng et al, 2019a ); only UV/PL in toluene (Okazaki et al, 2017 ; Pashazadeh et al, 2018b ; Zeng et al, 2018 ; Zheng et al, 2019b ); only UV/PL in DCM Ishimatsu et al, 2014 ; Pashazadeh et al, 2018a ; life time study on thin film (CBP host) Zeng et al, 2018 ; Zheng et al, 2019b ; life time study on thin film (zeonex host) (Pashazadeh et al, 2018a , b ) .…”
Section: Recent Progress On Multi-functional Tadf Emittersmentioning
confidence: 99%
“…Lateron Zeng et al ( 2018 ) reported three multifunctional organic emitters (5TzPmPXZ, 7TzPmPXZ, and 5,7TzPmPXZ) comprising PXZ-moiety integrated with electron-acceptor [1,2,4]triazolo[1,5-a]pyrimidine (TzPm) units, that exhibited TADF with excellent photoluminescence quantum yields (PLQYs) of 49–66%, along with MCL properties caused by transitions between microcrystalline and amorphous phases, in response to external mechanical stimuli. These D-A functional molecules exhibited small ΔE ST (0.06–0.10 eV) including good spatial separation between the HOMO and the LUMO, which is greatly encouraged by the large torsion angle between the donor and acceptor moieties (74.68 to 88.17°) resulting from the steric hindrance between the donor units and the neighboring phenyl ring, susceptible to RISC as well as TADF.…”
Section: Recent Progress On Multi-functional Tadf Emittersmentioning
confidence: 99%
See 1 more Smart Citation